Floristic description of areal and the stocks of raw materials of polygonum undulatum murr. growing in natural boundary Uytas (Trans-ili Alatau) (Experimental biology, 2015)
Results of the study medicinal plant Polygonum undulatum Murr. growing in the natural boundary Uytas (Ile Alatau) are listed in this article. Described population of Polygonum undulatum was found in Kaskelen gorge, in natural boundary Uytas, coordinates by GPS-navigation were N 43000.960/ и E 076038.117/, at an altitude of 2341 m, in the cereal-forb association with a rare participation of meadowsweet on a slope of southern exposure, steepness was 45-50 °, soil was black earth, projective cover has been 100%. As a result the population of Polygonum undulatum was investigated, geobothanical and floristic descriptions of plant communities have been carried out, specimens of species were collected in the herbarium. Also thickets area, productivity of land, operational reserve and possibility annual harvesting vegetable raw materials of Polygonum undulatum were installed in the Almaty region. Volume possible grass picking of Polygonum undulatum conforms collecting norms of medicinal plants
Keywords: Polygonaceae Juss.; Polygonum undulatum Murr.; medicinal plants; plant association; stocks of raw materials